2008
DOI: 10.1002/jtr.678
|View full text |Cite
|
Sign up to set email alerts
|

Destination product characteristics as useful predictors for repeat visiting and recommendation segmentation variables in tourism: a CHAID exhaustive analysis

Abstract: The present paper constitutes a segmentation research with the use of the exhaustive chi-squared automatic interaction detection tree analysis approach which, through the characteristics of a tourist destination, aims at the illustration of the English and German tourist groups and more specifi cally, (i) those who are repeat visitors of several tourist destinations and (ii) those who express a willingness to urge other people to visit geographic tourist destinations that the former have already visited. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
1
31
0
3
Order By: Relevance
“…This is because customers may express dissatisfaction with a product, but they rarely take the initiative to tell what they actually want (Kondo, 2000) from the suppliers. Besides, researchers generally attempt to measure the performance perception of the customers (2011) Accessibility McKercher (1998), Zhang and Lam (1999), Nicolau and Mas (2004), and Enright and Newton (2005) Infrastructure Yau and Chan (1990) Safety Shih (1986), Pizam and Mansfeld (1996), Baloglu and Uysal (1996), Dwyer and Kim (2003), Zhang et al (2004), Rodríguez-Díaz and Espino-Rodríguez (2008), Kao et al (2008), and Campo and Garau (2008) Museums and art galleries Baloglu and Uysal (1996) and Didascalou et al (2009) Hospitality and friendliness of the local people Mok et al (1995), Baloglu and Uysal (1996), Kozak (2001), Dwyer and Kim (2003), Campo and Garau (2008), Vassiliadis (2008), and Prayag (2011) Value Zhang et al (2004), Meng and Uysal (2008), Kao et al (2008), and Prayag (2011) Information Hudson and Shephard (1998), Chiang et al (2003), Vassiliadis (2008), and Moutinho et al (2011) Service quality Yau and Chan (1990), Mok et al (1995), Chadee and Mattsson (1996), Chiang et al (2003), Enright and Newton (2005), Meng and Uysal (2008), and Vassiliadis (2008) concerning product attributes using pre-structured questionnaires, which are unable to uncover the hidden expectations of...…”
Section: The Three-factor Theory Of Customer Satisfactionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is because customers may express dissatisfaction with a product, but they rarely take the initiative to tell what they actually want (Kondo, 2000) from the suppliers. Besides, researchers generally attempt to measure the performance perception of the customers (2011) Accessibility McKercher (1998), Zhang and Lam (1999), Nicolau and Mas (2004), and Enright and Newton (2005) Infrastructure Yau and Chan (1990) Safety Shih (1986), Pizam and Mansfeld (1996), Baloglu and Uysal (1996), Dwyer and Kim (2003), Zhang et al (2004), Rodríguez-Díaz and Espino-Rodríguez (2008), Kao et al (2008), and Campo and Garau (2008) Museums and art galleries Baloglu and Uysal (1996) and Didascalou et al (2009) Hospitality and friendliness of the local people Mok et al (1995), Baloglu and Uysal (1996), Kozak (2001), Dwyer and Kim (2003), Campo and Garau (2008), Vassiliadis (2008), and Prayag (2011) Value Zhang et al (2004), Meng and Uysal (2008), Kao et al (2008), and Prayag (2011) Information Hudson and Shephard (1998), Chiang et al (2003), Vassiliadis (2008), and Moutinho et al (2011) Service quality Yau and Chan (1990), Mok et al (1995), Chadee and Mattsson (1996), Chiang et al (2003), Enright and Newton (2005), Meng and Uysal (2008), and Vassiliadis (2008) concerning product attributes using pre-structured questionnaires, which are unable to uncover the hidden expectations of...…”
Section: The Three-factor Theory Of Customer Satisfactionmentioning
confidence: 96%
“…However, many academics found that there was an asymmetric relationship between the performance of the attribute(s) and overall customer satisfaction (Johnston, 1995;Matzler & Sauerwein, 2002;Mittal et al, 1998;Ting & Chen, 2002). While some product attributes (1) increase satisfaction when present, but do not increase dissatisfaction Current Issues in Tourism Yau and Chan (1990), Mok, Armstrong, and Go (1995), Lee, Var, and Blain (1996), Kozak (2001), Gallarza, Saura, and Garcia (2002), Dwyer and Kim (2003), Gooroochurn and Sugiyarto (2003), Nicolau and Mas (2004), and Filipović (2007) Culture Mok et al (1995), Baloglu and Uysal (1996), Gallarza et al (2002), van der Ark and Richards (2006), Enright and Newton (2005), Vassiliadis (2008), and Prayag (2011) Entertainment Boorstin (1964), Van Raaij (1986), Yau and Chan (1990), Mok et al (1995), Litvin and Ling (2001), Kozak (2001), Richards (2002), Zhang, Qu, and Tang (2004), Enright and Newton (2005), Meng and Uysal (2008), and Vassiliadis (2008) Activities for children Meng and Uysal (2008) Transportation Van Raaij (1986), Litvin and Ling (2001), Kozak (2001), Vassiliadis (2008), Moutinho, Albayrak, and Caber (2011), and Prayag (2011) Signage Prayag (2011) Nightlife Baloglu and Uysal (1996) and Enright and Newton (20...…”
mentioning
confidence: 95%
“…It has also been used to obtain information on expenditure levels using bo th demographic variables and those related to the trip's characteristics (Diaz-Pé rez, Bethencourt-Cejas & Alvarez-Gonzá lez, 2005) and to describe spending habits (Legoherel & Wong, 2006). Some studies have used it to identify future recommendations using product satisfaction, price and quality of service as independent variables (Chen, 2003); to know the likelihood of returning (Assaker & Hallak, 2012;Hsu & Kang, 2007) and to obtain information on intentions to recommend and visit the destination in the future (Vassiliadis, 2008).…”
Section: Choice Of the Criterion Variablementioning
confidence: 99%
“…Improving the quality of services is also recognised as one of the major strategies in consolidating destination competitiveness. Previous studies suggest that the receipt of excellent services reinforces the loyalty of current customers and increases the prospect of attracting new ones (Baker & Crompton, 2000;Chen, Chen, & Lee, 2009;Chen & Tsai, 2007;Hui, Wan, & Ho, 2007;Kozak, 2001;Lee, Graefe, & Burns, 2007;Murphy, Pritchard, & Smith, 2000;Nowacki, 2009;Oppermann, 2000;Um, Chon, & Ro, 2006;Vassiliadis, 2008;Yoon & Uysal, 2005;Zabkar, Brencic, & Dmitrovic, 2010). Thus a key strategy for consolidating destination competitiveness is to improve satisfaction and an understanding of the factors affecting the most the overall tourist satisfaction can be used to support destination supply strategies (Kim, 1998;Kozak & Rimmington, 1999, 2000.…”
Section: Introductionmentioning
confidence: 95%